A rare case of appendicitis incarcerated in an inguinal hernia - Smith-Singares, Eduardo (J Surg Case Rep, 2016)
Amyand's hernia was coined after Claudius Amyand (1660–1740), who was the first to describe the presence of a perforated appendix in a hernial sac and also was the first to perform a successful appendectomy in 1735. It is an exceptionally rare condition in which the hernia itself contains the appendix, which may not necessarily be inflamed. The presence of an inflamed appendix further contributes to the rarity of this case. We report a case of acute appendicitis brought on by its incarceration in the inguinal hernia.